Early Acquisition of Plural Morphology in a Classifier Language: Data from Korean 2-4 Year Olds. Issue 1 (2nd January 2022) - Ahn, Dorothy; Snedeker, Jesse
ABSTRACT: Korean is a classifier language in which bare nouns are not obligatorily number-marked. Children learning other classifier languages like Japanese and Mandarin are late in learning the plural morpheme. In this paper, we present two datasets that suggest that Korean plural marker - tul is acquired much earlier, in contrast to what has been previously claimed. In a comprehension study, we find that Korean children begin acquiring this morpheme by age 3, showing adult-like performance by age 4. We suggest that the higher frequency of plural marking on both types and tokens of nouns and the consistent marking of plural in the domain of definite nouns may facilitate Korean plural acquisition.